2014
DOI: 10.4321/s1137-66272014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Valor pronóstico del índice de Onodera en la supervivencia del cáncer colorrectal

Abstract: resuMenFundamento. El índice de Onodera (IO) combina los valores de los linfocitos circulantes y de la albúmina sérica y se ha utilizado como marcador del estado nutricional, postulándose recientemente en Japón y China su posible valor pronóstico en el cáncer colorrectal. Todavía no disponemos de datos sobre el valor predictivo del IO en una población occidental.Pacientes y métodos. Se revisaron 207 cánceres colorrectales resecados programada y consecutivamente, con intención curativa. Se calculó el IO pre-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Numerous studies have confirmed its predictive ability for adverse short-and long-term outcomes in CRC, including surgical site infections, pneumonia, septic shock, and poorer survival (16,32,33). Onodera and colleagues first proposed the Onodera's Prognostic Nutritional Index (OPNI), which has since been widely adopted to assess preoperative nutritional status and predict prognosis in various malignancies, including oral cavity, colorectal, and liver cancers (34)(35)(36). A high preoperative OPNI value was associated with better OS in CRC, establishing OPNI as an independent predictor for CRC cases (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have confirmed its predictive ability for adverse short-and long-term outcomes in CRC, including surgical site infections, pneumonia, septic shock, and poorer survival (16,32,33). Onodera and colleagues first proposed the Onodera's Prognostic Nutritional Index (OPNI), which has since been widely adopted to assess preoperative nutritional status and predict prognosis in various malignancies, including oral cavity, colorectal, and liver cancers (34)(35)(36). A high preoperative OPNI value was associated with better OS in CRC, establishing OPNI as an independent predictor for CRC cases (35).…”
Section: Discussionmentioning
confidence: 99%
“…Onodera and colleagues first proposed the Onodera's Prognostic Nutritional Index (OPNI), which has since been widely adopted to assess preoperative nutritional status and predict prognosis in various malignancies, including oral cavity, colorectal, and liver cancers (34)(35)(36). A high preoperative OPNI value was associated with better OS in CRC, establishing OPNI as an independent predictor for CRC cases (35). Consequently, preoperative identification of malnourished patients allows for early initiation of nutritional support, forming the foundation for enhanced recovery after surgery (ERAS) protocols, reducing postoperative complications, and improving long-term prognosis (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several hematological nutrition-related markers have been reported to hold potential prognostic value. Notably, Onodera and colleagues initially introduced the Onodera's Prognostic Nutritional Index (OPNI), which has since gained widespread acceptance as a tool for assessing preoperative nutritional status and predicting prognosis in various malignancies, including oral cavity, colorectal, and liver cancers [9,28,29]. A high preoperative OPNI value has been associated with poorer overall survival in CRC, thus establishing OPNI as an independent predictor for CRC cases [9].…”
Section: Discussionmentioning
confidence: 99%
“…Debido a la relación entre la respuesta inflamatoria sistémica y la progresión del tumor, se ha valorado la utilidad de diversos índices inflamatorios sobre el pronóstico en tumores de esófago, estómago, colon y recto, páncreas e hígado. Dentro de los parámetros que miden la respuesta inflamatoria destacaremos 5,13,16-20. Un estudio checo del año 2014, otro español del 2016 y el resto de los trabajos corresponden a Japón, Corea y China y se limitan a casos en los que se efectuó una gastrectomía con resección R0, registrando en el análisis multivariante un valor pronóstico significativo del IPN sobre la supervivencia 5,[21][22][23] . A diferencia de los estudios en países asiáticos, nuestra serie incluye a la totalidad de los pacientes con cáncer gástrico en el momento de su diagnóstico, e independientemente de su estadio de extensión y del tratamiento aplicado posteriormente.…”
Section: Discussionunclassified